1962
DOI: 10.1126/science.138.3548.1399
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscope Studies of Ribosomal Clusters Synthesizing Hemoglobin

Abstract: Nagy et al. As noted, their morphology 11. H. C. Urey, Nature 193, 1119 (1962); Science 137, 623 (1962). 12. The sample was obtained through the courtesy of Dr. E. P. Henderson.publications. The particles of the first class are in a morphological no-man'sland, and to establish their possible biological origin, new techniques and new criteria will have to be developed. As for particles of the second class, proof must be given that they are not terrestrial contaminants. This, like all negative proof, may be very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
99
2
1

Year Published

1964
1964
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 422 publications
(112 citation statements)
references
References 5 publications
10
99
2
1
Order By: Relevance
“…Such fine structures m a y represent artifacts of tissue fixation or staining. Nevertheless, similar structures have been seen in preparations of isolated ribosomes examined by the negative contrast technique (8).…”
Section: Structure Of the Polyribosomementioning
confidence: 66%
See 1 more Smart Citation
“…Such fine structures m a y represent artifacts of tissue fixation or staining. Nevertheless, similar structures have been seen in preparations of isolated ribosomes examined by the negative contrast technique (8).…”
Section: Structure Of the Polyribosomementioning
confidence: 66%
“…In mammalian reticulocytes, protein synthesis has been shown to proceed predominantly on ribosomes with sedimentation coefficients in excess of 110S (7)(8)(9). Electron micrographs of ribosome fractions isolated from lysed reticulocytes revealed that the rapidly sedimenting ribosomes (110S or greater, termed polyribosomes) are probably clusters of two or more 78S ribosomes (8).…”
Section: Introductionmentioning
confidence: 99%
“…7, 8, 10, and 15) may represent polysomes, or groups of ribosomes engaged in protein synthesis (Warner et al, 1962). If so, the existence of plastid "messenger" R N A may be postulated.…”
Section: Discussionmentioning
confidence: 99%
“…Since the original studies of polyribosomes (20,10,22), evidence has accumulated that most protein synthesis takes place on a structure, referred to as polyribosomes, which is composed of messenger RNA and a number of ribosomes. We examined mitotic and interphase HeLa cells for the presence of polyribosomal complexes.…”
Section: Hela Cellsmentioning
confidence: 99%